From Narrative of Innocence to Theology of Presence: Barthesian Semiotic Analysis on "Aku Ada" by Panji Sakti: Dari Narasi Kepolosan Menuju Teologi Kehadiran: Analisis Semiotika Barthesian pada Lagu ’Aku Ada’ Karya Panji Sakti - Haikal, M. Arsyad; Heri Kuseri; Moh. Ikhwan Faidlur Ruhman; Bambang Irawan (ABHATS: Jurnal Islam Ulil Albab, 2026)
This study examines the phenomenon of meaning transformation in the song Aku Ada by Panji Sakti, a work that presents a unique anomaly in the landscape of Indonesian Sufi music. Contrary to the general assumption that Sufi works are born from complex adult contemplation, genetic data from this research reveals that the song originated from the author’s spontaneous interaction with kindergarten children. The central problem lies in how a text born from the innocence of “childhood narrative” can transcend into a profound theological text for adult listeners. This study aims to dismantle this semiotic mechanism using a qualitative method with Roland Barthes’ Semiotics approach, supported by exclusive interview data as genetic context. The results reveal three key findings. First, at the connotation level, the children’s impulse to immediately help a friend (“when falling”, “when hungry”) is a pure manifestation of fitrah (innate nature), paralleling the ethics of Futuwwah. Second, at the myth level, the negation of fictional figures (“I am not Superman”) serves as a deconstruction of the “myth of power” and a critique of modern human ego inflation, while affirming the realism of physical presence. Third, the inspiration from the story of Prophet Ibrahim seeking a dining companion provides an intertextual basis for the ambiguity of the pronoun “Aku” (I), where the profane act of sharing food is reinterpreted as God’s manifestation (tajalli) through the availability of His servant. The conclusion confirms The Death of the Author theory, where the author’s pedagogical intent is surpassed by the text’s theological meaning production, proving that the path to gnosis (makrifat) can be found through the innocence of human nature. [Penelitian ini mengkaji fenomena transformasi makna dalam lagu ’Aku Ada’ karya Panji Sakti, sebuah karya yang menunjukkan anomali unik dalam lanskap musik sufistik Indonesia. Berbeda dengan asumsi umum bahwa karya sufistik lahir dari kontemplasi dewasa yang rumit, data genetik penelitian ini mengungkap bahwa lagu tersebut bermula dari interaksi spontan penulis dengan anak-anak Taman Kanak-Kanak (TK). Permasalahan utama penelitian terletak pada bagaimana teks yang lahir dari kepolosan ”narasi kanak-kanak” dapat mengalami transendensi makna menjadi teks teologis yang mendalam bagi pendengar dewasa. Penelitian ini bertujuan untuk membongkar mekanisme semiotis tersebut dengan menggunakan pendekatan kualitatif dan pisau analisis Semiotika Roland Barthes, didukung oleh data wawancara eksklusif sebagai konteks genetik. Hasil penelitian menunjukkan tiga temuan kunci. Pertama, pada tingkat konotasi, impuls anak-anak untuk segera menolong teman (”saat jatuh”, ”saat lapar”) merupakan manifestasi murni dari fitrah yang sejajar dengan etika futuwwah. Kedua, pada tingkat mitos, negasi terhadap tokoh fiksi (”Aku bukan Superman”) berfungsi sebagai dekonstruksi terhadap ”mitos kekuatan” (myth of power) dan kritik terhadap inflasi ego manusia modern, sekaligus menegaskan realisme kehadiran fisik. Ketiga, inspirasi kisah Nabi Ibrahim a.s. yang mencari teman makan menjadi landasan intertekstual bagi ambiguitas pronomina ”Aku”, di mana aksi profan berbagi makanan dimaknai ulang sebagai manifestasi (tajalli) Tuhan melalui ketersediaan hamba-Nya. Simpulan penelitian ini menegaskan berlakunya teori The Death of the Author, di mana intensi pedagogis pengarang dilampaui oleh produksi makna teologis teks, membuktikan bahwa jalan menuju makrifat dapat ditemukan melalui kepolosan fitrah manusia.]